Thirty- and 90-day Readmissions After Spinal Surgery for Spine Metastases: A National Trend Analysis of 4423 Patients. Issue 12 (15th June 2021) - Elsamadicy, Aladine A.; Koo, Andrew B.; David, Wyatt B.; Zogg, Cheryl K.; Kundishora, Adam J.; Hong, Christopher S.; Kuzmik, Gregory A.; Gorrepati, Ramana; Coutinho, Pedro O.; Kolb, Luis; Laurans, Maxwell; Abbed, Khalid
Abstract : Study Design: Retrospective cohort study. Objective: The aim of this study was to investigate differences in 30- and 90-day readmissions for spine metastases treated with decompression and/or fusion spine surgery in a nationwide readmission database. Summary of Background Data: Patients with metastases to the spine represent a particularly vulnerable patient group that may encounter frequent readmissions. However, the 30- and 90-day rates for readmission following surgery for spine metastases have not been well described. Methods: The Nationwide Readmission Database years 2013 to 2015 was queried. Patients were grouped by no readmission (non-R), readmission within 30 days (30-R), and readmission within 31 to 90 days (90-R). Weighted multivariate analysis assessed impact of treatment approach and clinical factors associated with 30- and 90-day readmissions. Results: There were a total of 4423 patients with a diagnosis of spine metastases identified who underwent spine surgery, of which 1657 (37.5%) encountered either a 30-or 90-day unplanned readmission (30-R: n = 1068 [24–.1%]; 90-R: n = 589 [13.3%]; non-R: n = 2766). The most prevalent inpatient complications observed were postoperative infection (30-R: 16.3%, 90-R: 14.3%, non-R: 11.5%), acute post-hemorrhagic anemia (30-R: 13.4%, 90-R: 14.2%, non-R: 14.5%), and genitourinary complication (30-R: 5.7%, 90-R: 2.9%, non-R: 6.2%). The most prevalent 30-day and 90-day reasons for admission were sepsis (30-R: 10.2%, 90-R: 10.8%), postoperative infection (30-R: 13.7%, 90-R: 6.5%), and genitourinary complication (30-R: 3.9%, 90-R: 4.1%). On multivariate regression analysis, surgery type, age, hypertension, and renal failure were independently associated with 30-day readmission; rheumatoid arthritis/collagen vascular diseases, and coagulopathy were independently associated with 90-day readmission. Conclusion: In this study, we demonstrate several patient-level factors independently associated with unplanned hospital readmissions after surgical treatment intervention for spine metastases. Furthermore, we find that the most common reasons for readmission are sepsis, postoperative infection, and genitourinary complications. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textIn this study, we demonstrate several patient-level factors independently associated with unplanned hospital readmissions after surgical treatment intervention for spine metastases. Furthermore, we find that the most common reasons for readmission are sepsis, postoperative infection, and genitourinary complications.